The metabolic syndrome in Morocco, a country in a nutritional transition, case of population of Sale - Samara, Ilyas (Université Ibn Tofail, Faculté des Sciences-Kénitra, 2017)
The evolution of food consumption in addition to the change of lifestyle towards an increasingly sedentary and westernized way of life has made Morocco, like other countries in transition, experiencing a rapid rise in obesity and undergoes an epidemiological transition accompanied by an increased burden of cardiovascular disease, and its risk factors, where lack of physical activity strongly cause many associated factors of the metabolic syndrome. This pathology qualified by the WHO in 1997 of the epidemic constitutes an emergent entity, which gathers at the same individual several metabolic anomalies, and predispose each one, with the cardiovascular risk Objective: The main purpose of this study was to determine the prevalence of metabolic syndromes and its co-factors in a Moroccan population (Sale, Morocco). Methods : A total of 300 subjects participated in the study, 46.7% males and 53.3% females, 56% in urban areas and 44% in rural areas, the mean age was 31.64 years (standard deviation : 12.47, range : 18-65). Data collection was done using a questionnaire developed and validated locally ; including social demographic data, with the measures of anthropometric parameters, All the blood test was measured by Hitachi biochemistry of the PLC 904 using enzymatic methods, All statistical analyzes were performed using SPSS software, Quantitative variables were described using mean, standard deviation (SD) and limits. Categorical variables were described using proportions and percentages. For the comparison of groups, we used the ᵡ2 test for frequencies and Student’s test for means. The confidence interval was adopted p<0.05. Results: The frequency of obesity and overweight were 11.6% and 35%. The elderly are the most affected, while the prevalence of the metabolic syndromes is 8.6%, with females and males respectively (57.7% and 42.3%). The study shows a significant association between High CRP level, Hyperuricemia and Obesity, and a close relationship between the occurrences of certain chronical no communicable diet-related diseases and the overweight and obesity leading eventually to the metabolic syndrome. Conclusion: It is time for health and nutrition policy-makers to review strategies to reduce the rise in obesity and its consequences, taking into account the increasing rate of the metabolic syndrome at the national level, as was the case in the region of Sale.
Keywords: Metabolic syndrome; Cardiovascular disease; Obesity; Inflammation; Physical activity.